Association of Acculturation Status With Beliefs, Barriers, and Perceptions Related to Cardiovascular Disease Prevention Among Racial and Ethnic Minorities - Edelman, Dana (2009)
Acculturation has been correlated with traditional cardiovascular disease risk factors. The purpose of this study was to examine the association between acculturation and health beliefs, barriers, and perceptions related to cardiovascular disease prevention. Racial/ethnic minority participants in the Family Intervention Trial for Heart Health were included in this analysis. Less acculturated minorities were more likely to have health beliefs that may impede prevention, have greater perceived susceptibility to disease, and believe in an external locus of control. Evaluating acculturation in clinical practice may be an opportunity to promote awareness, healthy behaviors, and prevention among immigrants.